The future of cancer therapy: exploring the potential of patient-derived organoids in drug development - Avci, Cigir Biray; Bagca, Bakiye Goker; Shademan, Behrouz; Takanlou, Leila Sabour; Takanlou, Maryam Sabour; Nourazarian, Alireza (Frontiers in Cell and Developmental Biology, 2024)
Cancer therapy is on the brink of a significant transformation with the inclusion of patientderived organoids (PDOs) in drug development. These three-dimensional cell cultures, directly derived from a patient's tumor, accurately replicate the complex structure and genetic makeup of the original cancer. This makes them a promising tool for advancing oncology. In this review, we explore the practical applications of PDOs in clinical drug screening and pharmacognostic assessment, as well as their role in refining therapeutic strategies. We provide insights into the latest advancements in PDO technology and its implications for predicting treatment responses and facilitating novel drug discoveries. Additionally, we address the operational challenges associated with incorporating PDOs into the drug development process, such as scaling up organoid cultures, ensuring consistent results, and addressing the ethical use of patient-derived materials. Aimed at researchers, clinicians, and key stakeholders in oncology, this article aims to succinctly present both the extraordinary potential and the obstacles to integrating PDOs, thereby shedding light on their prospective impact on the future of cancer treatment.